IPSILATERAL RENAL AGENESIS WITH MEGAURETER, BLIND END PROXIMAL URETER AND URETEROCELE IN AN ADULT - Ahmed, Ateeque (Journal of Ayub Medical College Abbottabad, 2017)
We reporting unilateral renal agenesis with ipsilateral ureterocoele, mega ureter and blind end proximal ureter in same patient first time as case report and has not been so far reported in local or international literature. Ultrasound, CT scan and intravenous pyelography performed which confirm the case. Patient presented with left lumber and pelvic pain on and off and history of recurrent urinary tract infection. Keywords: Renal agenesis; Megaureter; Ureterocoele